DETERMINAN KOMITMEN KERJA - Harras, Hadyati (Sekolah Menengah Kejuruan (SMK) Pustek, 2020)
Work does not only produce something, but also contributes to progress, especially in research institutions. But the role of leadership, competence, and motivation are among the factors that affect performance and competence. Therefore, this study aims to examine all three variables both partially and simultaneously. Quantitative was chosen because of its ease in interpreting the data obtained through the distribution of questionnaires. The structural equation model was chosen as a tool in analyzing statistical models. The results showed that the directly recommended model of commitment is competency. This explains that someone who is professional is more committed to work and is able to produce better assignments. Keywords: Leadership, Competence, Motivation, Commitment